Transition in self-identity: a sociological narrative of Tamil Muslims in Malaysia - Mushtaq Ahmed, Younus Ahmed; Basir, Norasikin (Taylor and Francis Inc., 2019)
The history of Tamil Muslims is intertwined with the Malay Archipelago since antiquity because of their geographical proximity. A community that has valued its heritage is now forced to reinvigorate itself and bridge through the current socio-economic and political scenario of Malaysia. The subsequent change in self-identity is viewed through the socio-historic approach of Anthony Giddens and the Assimilation Theory of Milton Gordon. The ethnicity with which the Tamil Muslims associate themselves has changed from Tamil to Malay, a shift highlighted among the younger citizens, carving a niche for themselves in society. The importance of a biographical narrative and the reflexivity of a modern society in the conceptualization of self-identity is noted in the case of Tamil Muslims in Malaysia.